Letting go and moving on: a grounded theory analysis of disengaging from university and becoming a registered nurse - Drury, Vicki; Francis, K.; Chapman, Y. (Elsevier, 2008)
This study describes the third phase of a constructivist grounded theory titled becoming a registered nurse. The study identifies that mature-aged students experience three phases in their university journey. These phases or subcategories are called taking the first step, keeping going and, finally letting go and moving forward. In this article mature students' experiences of letting go and moving forward are explicated. Data gathered through semi-structured interviews and focus groups with mature students from two rural university campuses in Australia are used to illustrate this construct. Grounded theory methods of concurrent data generation and analysis, coding, developing categories and memoing were used. It was found that mature students experienced anxiety as they transitioned out of university and into employment. Despite reports of a nursing crisis in rural Australia some students were unable to find employment in their local rural areas. These students allege that it is not the nursing shortage but rather a shortage of money to pay more nurses that is the real issue. Furthermore mature students did not have a sense of termination of their university studies as there was no formal recognition that they had completed at the time, rather the formal recognition, university graduation, occurred some months after completion.